Determination of Factors Affecting Oxygen Saturation During Transfer From the Operating Room to the Post-Anesthesia Care Unit - Arıcı Parlak, Emine; Ilkaz, Neslihan; Ayhan, Hatice; İyigün, Emine (The European Research Journal, 2026)
Objectives: This study aimed to determine the incidence of desaturation (SpO₂ ≤94%) during the transfer of postoperative patients from the operating room to the post-anesthesia care unit (PACU) without oxygen support and to identify factors associated with desaturation. Methods: This prospective cross-sectional study was conducted between July 2023 and July 2024 in the operating room and PACU of a training and research hospital. The sample consisted of 164 patients. Data were collected using the Oxygen Saturation Assessment Form. Post-extubation oxygen saturation levels were continuously monitored with a pulse oximeter during transfer to the PACU and until discharge. Results: During transfer from the operating room to the PACU, 43.3% of patients had SpO₂ ≤94%, and 8.4% of these patients had SpO₂